2022
DOI: 10.4143/crt.2021.828
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Mismatch Repair Deficiency/High Microsatellite Instability and Its Role as a Predictive Biomarker of Response to Immune Checkpoint Inhibitors in Gynecologic Cancers

Abstract: This study was to investigate the frequency of mismatch repair deficiency/high microsatellite instability (MMRd/MSI-H) in gynecologic malignancies and the efficacy of immune checkpoint inhibitors (ICIs) in patients with recurrent gynecologic cancers according to MMR/MSI status. Materials and MethodsWe conducted a multi-center retrospective review on the patients who were diagnosed with gynecologic cancers between 2015 and 2020. Their clinicopathologic information, results of immunohistochemistry staining for M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…However, it is important to note that the patients in the prior meta-analysis were mainly diagnosed with NSCLC and melanoma, which are known to respond favorably to ICIs, whereas patients in the present study were diagnosed with gynecologic malignancies, which have been reported to respond to ICIs in approximately 20% of cases regardless of MMR status. 11 12 Considering this, our results are encouraging, in that the response rate to ICI rechallenge among patients with recurrent gynecologic cancers, which have a relatively limited response to ICIs, was comparable to that reported in the prior meta-analysis.…”
Section: Discussionsupporting
confidence: 75%
“…However, it is important to note that the patients in the prior meta-analysis were mainly diagnosed with NSCLC and melanoma, which are known to respond favorably to ICIs, whereas patients in the present study were diagnosed with gynecologic malignancies, which have been reported to respond to ICIs in approximately 20% of cases regardless of MMR status. 11 12 Considering this, our results are encouraging, in that the response rate to ICI rechallenge among patients with recurrent gynecologic cancers, which have a relatively limited response to ICIs, was comparable to that reported in the prior meta-analysis.…”
Section: Discussionsupporting
confidence: 75%
“…Deficiency in DNA repair mechanisms results in a hypermutated genome, making it a surrogate marker of TMB, as well as a predictive biomarker for ICI therapy. Patients with MSI/dMMR showed a lasting response to pablizumab in multiple clinical trials ( 28 , 44 46 ), but the proportion of MSI mutations in cervical cancer is only approximately 3-%-11.3%, as shown in previous studies ( 47 , 48 ).…”
Section: Icis In Cervical Cancermentioning
confidence: 52%
“…In our preclinical study, we observed various tumor response rates, ranging from the highest (40%) in the JC model to the lowest (23%) in the E0771 model. In patients, ICI e cacies also vary based on the types of cancers or various predictive biomarkers including PD-L1, microsatellite instability (MSI)/mismatch repair de ciency (MMRd), tumor mutation burden (TMB), tumor in ltrating lymphocytes, and cytokines [18][19][20][21]. In our preclinical study, these different tumor response rates based on the syngeneic TNBC mice models may be due to different biological features in several aspects, such as tumor in ltrating lymphocytes, T cell proliferation, and cytokines just like in patients with cancer [22].…”
Section: Discussionmentioning
confidence: 99%